The Effectiveness Of Tofu Liquid Waste As A Natural Phytoestrogen For Mandibular Bone Of Ovariectomized Rats - Meilia Aquina; Nur Permatasari (Universitas Muhammadiyah Yogyakarta, 2012)
Estrogen is a steroid compound that has many benefits for the body's physiology.Hypoestrogenic women could have periodontitis in their mouth. Hormonereplacement therapy (HRT) is a therapy that used to reduce the disturbance causedby estrogen deficiency. However, HRT has many side effects. Theoretical studyshows that isoflavones in tofu liquid waste has an element of a steroid compound.The purpose of this study was to prove the effectiveness of isoflavones in the tofuliquid waste by examining the microscopic structure, estrogen receptor expressionand MDA levels in rat mandibular bone post-ovariectomy. This research methoduse a true experimental laboratory with randomized post test control group design.Twenty-four female wistar rats were divided randomly into six groups, consistedof a group of normal rat that does’nt ovariectomized (C1), 4 weeksovariectomized rats (C2), 8 weeks ovariectomized rats (C3) but no tofu liquidwaste was given, and 8 weeks ovariectomized rats that given tofu liquid waste atthe end of the 4th week of ovariectomy with three different doses (C4 = 1.2, C5 =6; C6 = 12 ml / kg). Histopathological slide used to see the changes resulted in anumber of osteoclasts, osteocytes, periodontal ligament width, alveolar boneheight, the amount of estrogen receptor expression and MDA levels. The resultsof statistical tests show that there is a difference in the rats between six differentgroups (ANOVA, p 0.05) and there is a close relationship between the dose ofthe tofu liquid waste with all parameter. The conclusion of this study is tofuliquid waste could improve the microscopic structure, estrogen receptorexpression and MDA levels in rat mandibular bone post-ovariectomy.